East Africa Climate-Smart Villages AR4D sites: 2016 Inventory - Bonilla Findji, Osana; Recha, John W.M.; Radeny, Maren A.O.; Kimeli, Philip (2017)
Inventory of CSA practices in East Africa’s ClimateSmart Villages.